Silent Conflict in High-profile Cities. Latin America and Beyond - Darmach, Krystian (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
This anthropological essay provides a meditation on mass tourism while analysing the mechanisms of conflict between the needs of mass tourism and the local urban environment, extraterritorial spaces that fit into the universal heritage of humanity. Historical districts/ entertainment districts in capital cities are discussed as extraterritorial areas treated as ambivalent, bypassed, business bases. The tourists themselves constitute thoroughly ambivalent figures as tame strangers, treated simultaneously as a potential source of maximum earnings and intruders.